1995
DOI: 10.1002/ajmg.1320560408
|View full text |Cite
|
Sign up to set email alerts
|

46,XY/47,XYY/48,XYYY karyotype in a 3‐year‐old boy ascertained because of radioulnar synostosis

Abstract: Chromosome analysis was performed on a 3-year-old boy because of bilateral radioulnar synostosis and demonstrated a mosaic karyotype 46,XY/47,XYY/48,XYYY. He had minor facial anomalies and mild intellectual delay. He appears to be the youngest patient reported with this rare chromosome complement. His father, mother, and brother had normal chromosomes. Fluorescence in situ hybridization (FISH) was performed on the propositus and his father with the Y chromosome heterochromatic probe (pHY3.4) to add to the eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The XYYY pattern is mostly observed with a mosaic pattern of XYY, XY and/or X, [6][7][8][9][10][11][12][13][14][15][16][17][18] and can also be seen as a single clone. Out of 15 cases, a mosaic pattern is seen in 7 cases, and pure XYYY is seen in 8 cases (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…The XYYY pattern is mostly observed with a mosaic pattern of XYY, XY and/or X, [6][7][8][9][10][11][12][13][14][15][16][17][18] and can also be seen as a single clone. Out of 15 cases, a mosaic pattern is seen in 7 cases, and pure XYYY is seen in 8 cases (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature on 40 affected males with 49XXXXY showed a high prevalence of musculoskeletal disorder where 75 % of them had radioulnar synostosis [ 27 ]. In addition, James et al [ 28 ] found a mosaic karyotype 46,XY/47,XYY/48,XYYY in a 3-year-old boy with bilateral radioulnar synostosis. Our patient with 47XXY/46XX with clinical features of Klinefelter and radioulnar synostosis adds further to the spectrum of mosaicism in variants of Klinefelter syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…CRUS may be an isolated condition, or it may be found with more than 65 nonaneuploid syndromes such as Apert, Poland, Carpenter, Crouzon, Antley Bixler, Saethre Chotzen, and Mandibulofacial Dysostosis (Rizzo et al ., ; Capra et al ., ; Linder et al ., ; Bhatt & Mehta, ; Panigrahi, ). CRUS has also been associated with sex chromosomal abnormalities, such as Klinefelter syndrome (XXY) (Mazauric‐Stüker et al ., ; James et al ., ; Syed & Quinton, ; Bhatt & Mehta, ). In addition, CRUS has been linked to Fetal Alcohol Syndrome (Burd & Martsolf, ).…”
Section: Differential Diagnosismentioning
confidence: 99%